The landscape of medical care consumption in Israel: a nationwide population cross-sectional study - Yoni Yosef; Alexander Kiderman; David Chinitz; Amnon Lahad (Israel Journal of Health Policy Research, 2022)
Abstract Background The Ecology of medical care was first published in 1961. The graphical square model showed that 75% of the population in the US and England experience a feeling of illness during a given month, 25% seek medical help and only one percent are hospitalized. In 2001, Green and colleagues found the same findings despite the many changes that occurred over the past decades. The frequency of illness, the desire for assistance and the frequency of seeking and getting medical assistance may differ in different populations due to cultural, economic, social, demographic background and local Health policy. This work describes the ecology of medical care consumption in Israel for the first time and examines the socio-demographic effects on consumption. Methods This is a Nationwide cross-sectional study. A telephone survey was conducted among a representative sample of the adult population (> 15 years) in Israel. Subjective morbidity rate in the preceding month, the rate of those considering medical assistance and those who got assistance were calculated. Correlation between socio-demographic variables and patterns of morbidity and medical care consumption was examined using a t-test and chi square for continuous quantitative and categorical variables. Logistic regression was used for multivariate analysis. Results A total of 1862 people participated; 49.5% reported having symptoms in the previous month, 45% considered seeking medical advice, 35.2% sought out medical assistance and only 1.5% were hospitalized. The vast majority chose to contact their family physician (58%) and the primary care setting provided their needs in 80% of the cases; Subjective morbidity and medical care consumption differed significantly between Israeli Jews and Arabs. Gaps in the availability of medical services were observed as residents of the periphery forewent medical services significantly more than others (OR = 1.42, p = 0.026). Conclusions Subjective morbidity is less common in Israel than in other countries, but paradoxically consumption of medical services is higher. An Israeli who feels ill will usually consider receiving assistance and will indeed receive assistance in most cases. However, a greater tendency to forego medical services in the periphery indicates barriers and inequality in the provision of health services. Different cultural perceptions, lack of knowledge and low accessibility to medical services in the periphery probably contribute to the contrast shown between low consumption of medical services and high prevalence of chronic illness in Arab society. The prevailing preference for family medicine and its ability to deal with most requests for assistance suggest that strengthening family medicine in the periphery may reduce those barriers and inequalities.